A new transducer receive transfer function calibration method: application to microbubble backscattering cross-section measurements at high frequency. - Sprague, MR; Chérin, E; Foster, F (2011)
When comparing acoustic scattering experiments with theory, the relationship between the pressure generated by a scatterer at the surface of a transducer and the induced voltage must be known. Methods have been previously proposed to measure the receive transfer function that rely on several assumptions. A new, experimental method for measuring the acoustic response of a spherically-focused transducer, using a hydrophone at twice the focal distance, is proposed that requires a minimum number of assumptions and calculations. The receive transfer function of a spherically-focused, high-frequency transducer was calculated, and found to be within 10% of the receive transfer function calculated assuming reciprocity. Further, using the receive transfer function, the effective backscattering cross-section of bound microbubbles interrogated at 30 MHz was measured to be, on average, 65% of the geometric backscattering cross-section, with significant size-independent variability. These results give insight into selecting the optimal microbubble size distribution for linear microbubble imaging at high frequencies.